2005
DOI: 10.1038/sj.gt.3302552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a synthetic CArG promoter for nitric oxide synthase gene therapy of cancer

Abstract: Nitric oxide synthase gene therapy has been shown to be effective at inducing apoptosis in experimental tumours and sensitizing them to radiotherapy. We have also shown that expression of inducible nitric oxide synthase (iNOS) can be effectively restricted to the tumour volume by the use of the radiation inducible promoter (WAF1) to drive the transgene in clinically relevant protocols. A synthetic construct (pE9), incorporating nine radiosensitive CArG elements from the Egr1 promoter, has recently been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 36 publications
(51 reference statements)
2
32
0
Order By: Relevance
“…We have also shown previously that WAF1 could be used to drive iNOS expression in vivo and could sensitize both HT29 and RIF1 tumours to a single therapeutic radiation dose. 7,18,19 We also demonstrated that the iNOS levels were increased following direct injection of this construct into RIF1 tumours within 24 h with levels significantly elevated up to 5 days; similar results were seen with the HT29 xenograft, both before and after an inducing dose of radiation, to activate the WAF1 promoter. 18,19 We now wanted to test this approach using fractionated radiation schedules in vivo at clinically relevant doses per fraction.…”
Section: Growth Delay Of Rif-1 and Ht29 Tumours In Vivo Following Frasupporting
confidence: 63%
See 1 more Smart Citation
“…We have also shown previously that WAF1 could be used to drive iNOS expression in vivo and could sensitize both HT29 and RIF1 tumours to a single therapeutic radiation dose. 7,18,19 We also demonstrated that the iNOS levels were increased following direct injection of this construct into RIF1 tumours within 24 h with levels significantly elevated up to 5 days; similar results were seen with the HT29 xenograft, both before and after an inducing dose of radiation, to activate the WAF1 promoter. 18,19 We now wanted to test this approach using fractionated radiation schedules in vivo at clinically relevant doses per fraction.…”
Section: Growth Delay Of Rif-1 and Ht29 Tumours In Vivo Following Frasupporting
confidence: 63%
“…5,6 We have also shown that a synthetic construct (pE9), incorporating nine radiosensitive CArG elements to drive inducible nitric oxide synthase (iNOS), was more effective than a constitutive CMV-driven construct both in vitro and in vivo. 7 The tumour microenvironment itself also presents opportunities to specifically target tumour tissue. Due to the ineffectual blood vessel network that exists in tumours, there are areas of low oxygen tension that are problematic for conventional cancer treatments in that they are inherently resistant to radio-or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrite Production-Nitrite production is measured using a nitric oxide quantitation kit (Active Motif, Ede, The Netherlands) (45). Nitrite is quantified by the addition of Griess reagent, which converts nitrite into a purple-colored azo compound.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous physiological study of an ex vivo rat tail artery treated with pE9/iNOS showed rapid and more pronounced vasodilatation compared to CMV/iNOS-treated preparations, supporting our hypothesis of a positive feedback loop increasing the activation of the pE9 promoter. 10 Furthermore, significant antitumour effects were reported after a single 25 mg injection of the pE9/iNOS construct into intradermal radiation-induced fibrosarcoma (RIF)-1 tumours. A fourfold increase in protein expression and an eightfold increase in nitrite concentration within the tumour resulted in a 7-day delay in tumour growth as compared with untreated tumours.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In a previous study we have shown that the CArG/iNOS construct may form a positive feedback loop, whereby the production of NO K , coupled with the elevated endogenous levels of NO K in tumours, resulted in the formation of ROS that in turn further activate the promoter. 10 Many tumours exhibit hypoxic regions reducing the effectiveness of radiotherapy. 6 Previously, we have shown that iNOS gene therapy diminished radioresistance observed under hypoxic conditions, thereby making it an ideal strategy for the treatment of solid tumours.…”
Section: Introductionmentioning
confidence: 99%